Effects of Cycle Ergometer Training on Heart Rate Recovery and Mind Fullness in NYHA class I, II Heart Failure Patients - Irfanullah, Mehwish Waseem, Naveed Yaqoob, Saleh Shah, Iqbal Tariq, Fatima Chaudhary, Umar Ibrahim, Zil E Huma, Nasir Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine effect of Cycle ergometer on heart rate recovery and mindfulness in NYHA Class I and II heart failure pts. Study design: The study was a randomized controlled trial. Place and duration: Total study duration was 6 months, carried out at Rawal general and dental hospital Islamabad. Methodology: 38 patients were divided into the Control and experimental group. The control group received only conventional Therapy at home and the hospital on the third and 6th weeks for a supervised conventional therapy session. The experimental group received conventional therapy and cycle ergometer training thrice weekly for six weeks. Baseline demographic data, Vitals, HRR1, HRR2, and MAAS scores were gathered from both groups and compared after six weeks. Results: The mean age of the control group was (46.37±4.43) and of the experimental group (was 50.47±9.22). The MAAS score was significant with a p-value (< 0.05). HRR1 and HRR2 were also significant, with a p-value (<0.05). Conclusion: This study showed that cycle ergometer exercise training significantly improved heart rate recovery in NYHA Class I and II heart failure patients and improved mindfulness. Keywords: Heart failure, Heart Rate Recovery 1(HRR1), Heart Rate Recovery 2 (HRR2), Mindful Attention Aware Scale